Insights on the nature of language from the study of gesture units - Cienki, Alan (Categories and Units in Language and Linguistics, 2020)
Gesture categories and gesture units are characterized according to both formal and functional criteria. The resultant functional types fall along a continuum according to the degree to which their tokens have conventionalized symbolic status. The more conventional the form/meaning pairing, the more straightforward it is to identify gestures as units. Most types of gesture categories are best viewed as having prototype structures, rather than a category structure with strict boundaries. This view on gesture aligns with some contemporary thinking about linguistic categories, which also espouses a prototype approach. The result is a coherent picture of how gesture interactions with different categories and units of spoken language, taking human audio-visual communication as dynamic and polysemiotic in nature.